Redesign de produtos do vestuário para mulheres motociclistas - Silva, Regiane Nogueira da (2014)
This work proposes a study of clothing used of motorcyclists woman. In accordance with the field search accomplished in the city of Apucarana-PR, perceptivity that the existence products present products represent products that attend only the function necessity. Of this, the investigation with based upon on design to aggregate value in the products making ergonomic and textile technology. The application of knowledge proposes pieces with practically, security and fashion present tendency.